2023
DOI: 10.7759/cureus.45892
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Titanium Oxide Nanoparticles With Rosemary and Ginger and Their Bactericidal Action Against Staphylococcus aureus

Thamarai Selvi V T,
Jerry Joe Chokkattu,
Neeharika S
et al.

Abstract: Introduction: Titanium oxide (TiO 2 ) nanoparticles (NPs) have significantly proved to be highly useful in restorative materials, dental adhesives, sealants, cements, and other dental applications to prevent microbial colonization and reduce the risk of infections. The present study was aimed at developing a dental material with antibacterial properties by combining titanium oxide NPs using ginger and rosemary extracts. Materials and methods: The formulation was prepared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Many studies have reported that due to the many phytochemicals (phenolics, terpenoids, etc), plant extract can act as a reducing and stabilizing agent by converting metal salt into nano form [16,17]. There are many studies reported synthesis of metallic nanoparticles using plants extract of jasmine flower [18], papaya [19], Piper nigrum, Coriandrum sativum, Syzygium aromaticum [20], rosemary, ginger [21], Impatiens rothii [22], Terenna asiatica [23], Garcinia mangostana [24], Iranian propolis [25], mango [26].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that due to the many phytochemicals (phenolics, terpenoids, etc), plant extract can act as a reducing and stabilizing agent by converting metal salt into nano form [16,17]. There are many studies reported synthesis of metallic nanoparticles using plants extract of jasmine flower [18], papaya [19], Piper nigrum, Coriandrum sativum, Syzygium aromaticum [20], rosemary, ginger [21], Impatiens rothii [22], Terenna asiatica [23], Garcinia mangostana [24], Iranian propolis [25], mango [26].…”
Section: Introductionmentioning
confidence: 99%